What (cyber)reading for the (cyber)classroom? - De Jorge, Maria-Goicoechea; Sanz, Amelia (Neohelicon, 2009)
In the present paper, we take as a starting point the debate on the relationshipsbetween the changes in writing supports and the changes in reading rituals, defending theneed to pluralize the models and functions of literary reading so as to be able to approach different typologies of literary digital texts. Firstly, after revising and situating in a historical context the different types of reading rituals that the print text has developed, wereflect upon the type of reading that the academia is implicitly demanding in this newcontext through its use of ICCT and the design of learning sites. Secondly, we discuss how our readers, the students, are adjusting to the new digital literature and how can the teacher guide them through this permanently morphing scenario. We argue about the need to develop functional models for digital literary readings, and in the final section of the paper, we offer several reading strategies that can help teachers and students build a bridge between print and digital literary texts.
Keywords: digital literature; lecture numérique; stratégie de lecture